2016
DOI: 10.1111/hojo.12164
|View full text |Cite
|
Sign up to set email alerts
|

Prisoner Relationships with Voluntary Sector Practitioners

Abstract: Recent scholarship has indicated that the voluntary sector is becoming increasingly important in marketised penal service delivery. However, market policy reforms are thought to pose risks to distinctive voluntary sector work with prisoners. Although commentators have suggested that the voluntary sector and its staff make distinctive contributions to prisoners, these have long been poorly understood. This article uses original interview data to demonstrate that voluntary sector practitioners can offer prisoner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
(96 reference statements)
1
23
0
2
Order By: Relevance
“…The potential resonances in outsider status or sense of alterity shared between prisoners and practitioners illustrates a different form of endeavour existing below the radar in, and among, the work of the penal voluntary sector in England and Wales. This presents a challenge to more widely accepted notions of ‘a distinctive “voluntary sector” ethos of compassion and rehabilitative approach’ (Tomczak and Albertson , pp.65–6). Indeed, other‐ness and outsider‐ness may serve as the starting point of encounters between service user and practitioner acting as a common point of reference and source of shared identification.…”
Section: Summary Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The potential resonances in outsider status or sense of alterity shared between prisoners and practitioners illustrates a different form of endeavour existing below the radar in, and among, the work of the penal voluntary sector in England and Wales. This presents a challenge to more widely accepted notions of ‘a distinctive “voluntary sector” ethos of compassion and rehabilitative approach’ (Tomczak and Albertson , pp.65–6). Indeed, other‐ness and outsider‐ness may serve as the starting point of encounters between service user and practitioner acting as a common point of reference and source of shared identification.…”
Section: Summary Discussionmentioning
confidence: 96%
“…We would like to see this as a focus for future research. Though it is beyond the scope of this discussion to examine these relationships, a repeated finding of research into penal programmes is their importance for outcomes of interventions and sentences (Barry ; Burnett ; Burnett and McNeill ; Harris ; Leibrich ; McIvor ; Miller and Rowe ; Rex ; Rowe and Soppitt ; Tomczak and Albertson ; Walker ).…”
Section: Summary Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little empirical evidence about the quality and nature of the relationships that develop between voluntary sector workers (whether paid staff or volunteers) and the individuals on the ‘receiving end’ of the service. The literature contains some hints that relationships in the penal voluntary sector, where organisations are able to keep a distance from the statutory requirements of recording and reporting, offer something distinctively genuine and human (Tomczak and Albertson ; Vennard and Hedderman ). However, as with other aspects of penal voluntary sector practice, this concept of distinctive difference remains undertheorised.…”
mentioning
confidence: 99%
“…Second, the effective offender engagement model developed by NOMS (Copsey and Rex 2013) based primarily on risk-need-responsivity principles (Bonta and Andrews 2010) for probation practitioners, at first glance does not appear to be wholly applicable to the terms of VCS engagement with offenders. Commentators have suggested that the involvement of VCS agencies with offenders in the community and custody has a different function and role from that of probation and prison staff (Maguire 2012(Maguire , 2016Martin et al 2016;Meek, Gojkovic and Mills 2010;Mills, Meek and Gojkovic 2011;Tomczak 2017;Tomczak and Albertson 2016). Third, given the greater reliance on VCS services to work with offenders, there is a need for VCS provision to be more evidence based.…”
mentioning
confidence: 99%